Benefit and risk analysis of an automatic meter reading system for electricité du Liban - Ghajar, Raymond F. (2012)
This paper summarizes the beneﬁt and risk analysis of a study for modernizing the electricity metering, billing and revenue collection systems for ´Electricit´e du Liban, the national power company of Lebanon. A cost/beneﬁt analysis of the modernized system shows that the system has a payback period of 3.05 years. Like all economic evaluations, there are uncertainties associated with the estimated costs and beneﬁts which could increase the value of the payback period. The purpose of this paper is to identify the im- portant risks and other uncertainties that could aﬀect the economic feasibility of the project and assess the potential impacts of these uncertainties. To achieve this objective, a Monte-Carlo type analysis is employed and a distribution of the expected payback period is determined. The beneﬁts are modelled in two ways, using triangular and uniform distributions, while the costs are modelled using uni- form distributions only. The choice of triangular distribution shows conﬁdence in the initial estimates whereas using a uniform distri- bution implies that the variables could deviate substantially from the initial estimates. The payback period determined from both models is around 3 years (3.18 years when all input variables are modelled using uniform distributions, and 3.12 years when uniform distributions are used for costs and triangular distributions are used for beneﬁts) with a maximum range of 2.2–4.7 years. The results of the risk analysis also indicate that the beneﬁts from an aggressive revenue recovery process (identifying and reducing fraud and theft) have the most inﬂuence on reducing the project payback period. In summary, this paper shows that the proposed modernization project is economically feasible.